Table of Content - -, (Arab Journal for Sciences and Research Publishing, 2023)
Table of Content:1. Verbal estimates in The Holy Quran and their impact on deriving Fiqh rulings related to worshipDr. Ahmed Abdo Ahmed Al-Ghdarj2. Towards a national ecosystem to create scientists and sovereign knowledgeDr. Bandar A. Al-Saud , Dr. Abdulhamid A. Al-Abduljabbar3. Manifestations of religious dialogue between Muslims and Jews Secular Jews as a modelMrs. Maha Dahawi Al-Shamari4. A study on the Chinese translation Strategies of Arabic Proverbs from the Perspective of Cultural TranslationMrs. Yuan Linxian5. A pragmatic Analysis of the Interrogative Illocutionary Acts with Reference to Arabic Text of Surah As- Saffat in the Holy Qur’ānDr. Adel Ahmed Abdullah Al- Mekhlafy , Prof. Abdusalam Mohammed Ghaleb Al- Ghrafy6. Analysing the Power of Language in a Political TextMrs. Suhair Adel Abdulamir7. Application of Abaoub- Shkheam Transform for Solving Linear Partial Integro – Differential EquationsDr. Suad Mawloud Zali8. Constrained Probabilistic multi-source Continuous Review Inventory Model with Dagum and Kumaraswamy-Dagum distributionsCo-Prof. Hala Ali Fergany ,Dr. Amani Saeed Alghamdi , Mrs.Amsha Zayed Almutairi
Keywords: Arab Journal of Sciences & Research Publishing